Prevalence of Hyperglycemia and Its Association with Breast Cancer Stage: A Case-Control Study in Meru County, Kenya - Herbert W. Kibebe; Eric M. Muchiri; Maryjoy Kaimuri (Journal of Medicine, Nursing and Public health, 2026)
Background: Hyperglycemia, a hallmark of type 2 diabetes mellitus (T2DM), is increasingly implicated in breast cancer pathogenesis through the Warburg effect, hyperinsulinemia, and chronic inflammation. Understanding its prevalence and relationship with breast cancer stage in Sub-Saharan African populations remains critical for informing context-specific screening strategies. Objectives: (1) To determine the prevalence of hyperglycemia (HbA1c ≥6.5%) among breast cancer patients compared to controls; and (2) to identify glycated hemoglobin (HbA1c) as a biomarker associated with different breast cancer stages. Methods: A hospital-based case-control study enrolled 285 women (142 histologically confirmed breast cancer cases, 143 controls with non-cancerous breast masses) at Meru Teaching and Referral Hospital, Kenya. HbA1c was measured using a validated immunoturbidimetric analyser. Chi-square tests, independent samples t-tests, one-way ANOVA with Tukey’s HSD post-hoc analysis, and ROC curve analysis were applied. Results: Hyperglycemia was documented in 84.5% of cases versus 34.3% of controls (p < 0.001). Mean HbA1c was 6.89±0.75% in cases versus 5.82±0.71% in controls (t(283) = 12.445, p < 0.001). ROC analysis identified HbA1c ≥6.5% as the optimal threshold (AUC = 0.751, sensitivity 84.5%, specificity 65.7%). Stage IV cases had the highest HbA1c (7.56±0.87%), with a significant post hoc difference between Stage II and Stage IV (mean difference = 0.782%, p = 0.031), although the overall ANOVA was borderline (F(3,139) = 2.599, p = 0.055). Conclusion: HbA1c ≥6.5% is a prevalent and clinically meaningful biomarker in this Kenyan breast cancer population, with elevated values clustering at advanced disease stages. Integration of HbA1c into routine breast cancer screening and staging protocols is warranted.